Fracture Toughness, Surface Roughness and Fluoride Release of Glass Ionomers After Immersion in Athletic Drinks. - M. Hamouda Ibrahim; A. Ibrahim Dina; E. Alwakeel Essam (Journal of Dentistry And Oral Implants, 2014)
Objectives: This study was conducted to evaluate the effect of sport and energy drinks on conventional and resin-modified glass ionomer restorative materials regarding fracture toughness, surface roughness and fluoride release. Methods: The restorative materials used were conventional and resin-modified glass ionomers. Sport drinks used were Gatorade Perform 02 and Pocari sweat, while the energy drinks were Red Bull and Power Horse. Specimens were prepared and divided into five groups according to the immersion media (distilled water, two sport drinks and two energy drinks) for 1 and 7 days. The fracture toughness was determined using three-point bending method. Surface roughness was measured using surface profilometer. Fluoride release was determined using a conventional ion chromatograph testing unit. The data were analyzed using three-way ANOVA and Least Significant Difference test. For comparison between the two materials under each condition, t-test was used. Results: There was no significant difference in fracture toughness between sport, energy drinks and distilled water at the different time intervals except for conventional glass ionomer after 7 days. Resin-modified glass-ionomer exhibited smoother surfaces more than conventional one in sport and energy drinks after 1 day. After 7 days, both conventional and resin-modified glass ionomers showed greater surface roughness. Both conventional and resin-modified glass ionomers release more fluoride in acidic beverages than distilled water. Conclusions: The effect of sport and energy drinks on the fracture toughness may depend on the composition and acidity of drink. Fluoride release increased with the consumption of sport and energy drinks.
Keywords: sport drinks